1998
DOI: 10.2214/ajr.171.1.9648782
|View full text |Cite
|
Sign up to set email alerts
|

Ductectatic mucinous cystic neoplasms of the pancreas: evaluation with MR cholangiopancreatography.

Abstract: T he pathologic and radiologic features of ductectatic mucinous cystadenoma and cystaclenocarci nomaof the pancreashavebeenclarified [1â€"5]. These tumors originate from ductal epithelial cells within the pancreaticduct branches.This entity is characterized by a cystic dilatation of a branchof the pancreaticduct that often contains thick mucin, frequently locatedin the uncinate process of the pancreas [2]. Macroscopically, the lesion is covered with thin pancreatic paren chyma and consists of a conglomeration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(22 citation statements)
references
References 8 publications
(9 reference statements)
1
21
0
Order By: Relevance
“…These results agree with those of previous studies [2][3][4]. Therefore, demonstration of connection between cystic lesions and the main pancreatic duct is helpful in the diagnosis of branch duct-type IPMTs, although this finding alone does not allow us to rule out other cystic lesions [4][5][6][7][8][9]. Also in the present study, all of the 26-branch duct-type IPMTs were found to have connection with the main pancreatic duct, while only one of the 13 other cystic lesions showed such connection.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These results agree with those of previous studies [2][3][4]. Therefore, demonstration of connection between cystic lesions and the main pancreatic duct is helpful in the diagnosis of branch duct-type IPMTs, although this finding alone does not allow us to rule out other cystic lesions [4][5][6][7][8][9]. Also in the present study, all of the 26-branch duct-type IPMTs were found to have connection with the main pancreatic duct, while only one of the 13 other cystic lesions showed such connection.…”
Section: Discussionsupporting
confidence: 91%
“…Four radiologists (9,11,13, and 15 years experience in abdominal image interpretation) who were blinded to other imaging findings and the diagnosis interpreted the images in cine mode. Each observer assessed three sets of images (0.5 or 1 mm axial images, MPR images, and both axial and MPR images) independently at intervals of a least 2 weeks.…”
Section: Image Processing and Interpretationmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also known that cystic tumor of the pancreas is demonstrated with high signal intensity by MRCP, because of the high sensitivity of the MRCP sequence to fluid-filled structures (17). Therefore, several studies on the diagnosis of cystic tumor of the pancreas using MRCP have been conducted in recent years (18).…”
Section: Discussionmentioning
confidence: 99%